In Situ Self‐Assembly of Fluorogenic RNA Nanozipper Enables Real‐Time Imaging of Single Viral mRNA Translation - Zhang, Yu‐Peng; Wang, Zhi‐Gang; Tian, Yi‐Fan; Jiang, Lin‐Han; Zhao, Liang; Kong, De‐Ming; Li, Xing; Pang, Dai‐Wen; Liu, Shu‐Lin (Angewandte Chemie International Edition, 2023)
Real‐time visualization of individual viral mRNA translation activities in live cells is essential to obtain critical details of viral mRNA dynamics and to detect its transient responses to environmental stress. Fluorogenic RNA aptamers are powerful tools for real‐time imaging of mRNA in live cells, but monitoring the translation activity of individual mRNAs remains a challenge due to their intrinsic photophysical properties. Here, we develop a genetically encoded turn‐on 3,5‐difluoro‐4‐hydroxybenzylidene imidazolinone (DFHBI)‐binding RNA nanozipper with superior brightness and high photostability by in situ self‐assembly of multiple nanozippers along single mRNAs. The nanozipper enables real‐time imaging of the mobility and dynamic translation of individual viral mRNAs in live cells, providing information on the spatial dynamics and translational elongation rate of viral mRNAs. We developed a genetically encoded RNA nanozipper that allows real‐time imaging of the mobility and dynamic translation of individual viral mRNAs by in situ self‐assembly in live cells, providing information on the spatial dynamics and translation elongation rates of viral mRNAs. This can provide an effective method to monitor the translation activity of individual viral mRNAs in live cells.